Multilayer Structure Technique for Improving Determination of Electromagnetic Properties of Radar Absorbers Based on Two-Layer Method and Flanged Rectangular Waveguide Probe - Abdulkadhim Ameen Hassan; Janan Hammed Saadie (IAES Indonesian Section, 2020)
This paper presents further development of utilization of two-layer method to perform nondestructive electromagnetic properties determination of planar radar absorbers using flanged open-ended rectangular waveguide probe. A multilayer structure of three layers was proposed to improve the measured results of these parameters obtained using two-layer method. These layers were arranged such that the test material is sandwiched between two known low loss materials to provide the needed two independent reflection coefficients necessary to extract them at different conditions of testing. The proposed structure was aimed to decrease the effect of direct backing of test material by metal plate, which influences measurement accuracy if two-layer method is used. The structure permits a suitable electric field interrogation in test material and decreases the influences of both radial and surface waves. FDTD method was adapted for modeling the problem geometry to calculate the reflection coefficients since a probe with finite flange size is used. Measurements were carried out using the proposed technique to determine complex permittivity and complex permeability of several radar absorbers over X-band applications of microwaves. In comparison with both single-layer and two-layer methods results, the measured results of these parameters agreed well with the published data. by companies and literatures.